Estimation of the Occurrence Time of Thaumasite Sulfate Attack on Tunnel Lining Concrete - Chongbang Xu; Xiaojing Gao; Xuefeng Li; Kaishun Zhang (Advances in Civil Engineering)
The thaumasite sulfate attack (TSA) on tunnel concrete structure has been reported increasingly in the past decades. Previous investigations on the formation of thaumasite were focused on identifying the deterioration products and reaction mechanisms, while the occurrence time of TSA on tunnel concrete structures was not reported. A highway tunnel exposed to TSA was reported in the present study. The development of tunnel diseases and results of experimental tests conducted in the tunnel and in the laboratory were analyzed to investigate the occurrence time of TSA on concrete. Results revealed that the thaumasite was formed in a range of 18 to 36 months after the construction of Dugongling tunnel. The preconditions for the formation of thaumasite on tunnel concrete structures are available in Shanxi Province, China, due to the special conditions of stratum lithology and climate. The compositions of corrosion products of lining concrete under TSA varied for site studies and for laboratory tests. Site investigations on TSA on tunnel lining concrete should be paid more attention in further research.